Menstrual Regulation Services and Post Menstrual Regulation Care in the Context of Bangladesh - Tasnim, S (Nepal Journal of Obstetrics and Gynaecology, 2012)
Menstrual regulation (MR) program is an important component of reproductive health services that had been introduced to prevent abortion related deaths in Bangladesh. The service is provided through a nationwide network of government and non government facilities. Proper selection of cases and maintenance of quality of services are essential to prevent any complication and optimize its use. NJOG 2011 Nov-Dec; 6 (2): 53-55 DOI: http://dx.doi.org/10.3126/njog.v6i2.6760